Detection of Peronospora manshurica in imported soybean and analysis of oospore viability in storage warehouses in Ternate City, Indonesia - Khori Arianti; Suryati Tjokrodiningrat; Suratman Sudjud (Universitas Lancang Kuning, 2023)
The soybean needs of the people in Ternate are fulfilled by imported soybeans that enter through Surabaya. The process of transporting imported soybean seeds from Surabaya to the port of Ternate and storage in warehouses may lead to contamination with Peronospora manshurica fungus, which poses a risk of spreading to soybean crops in Ternate. This study aims to detect the presence of P. manshurica fungus, viability, and growth of P. manshurica oospores in the imported soybean storage warehouses in Ternate. The study was conducted using a combination of qualitative and quantitative methods. The qualitative method was carried out through an exploratory approach, while the quantitative method used a randomized block design (RBD) consisting of four treatments, i.e., G.Tbsi, G.Jbla, G.Tfra, and G.Tfrb, with five replications. The observation variables included disease occurance, presence, and characteristics of oospores, as well as oospore growth and viability percentage. The results showed that the average disease occurance in the soybean storage warehouses was highest in the sample of soybeans from the Tfrb warehouse at 1.88%, followed by the Jbla, Tfra, and Tbsi warehouses at 1.44%, 1.41%, and 1.24%, respectively. The study also found P. manshurica fungus in all four soybean storage warehouses in Ternate, with a viability percentage of G.Tbsi, G.Jbla, G.Tfra, and G.Tfrb were 25.8%, 28.8%, 27.4%, 26.5% respectively. These findings indicate the potential for disease spread to soybean crops in Ternate, thus necessitating appropriate preventive measures to address this problem.